Durability of high performance concrete incorporating normal and ultra fine ground granulated blast furnace slag - Loo, Shu Ning. (2012)
Carbonation and chloride induced corrosion are the two main reasons for corrosion of steel bars in concrete. Chloride induced corrosion is the primary reason for deterioration of concrete structures especially for High Performance Concrete (HPC) which are fully saturated and this inhibits carbonation. High expenditures are required to repair the corroded structures. Hence, it is important to study the durability of the concrete to ensure that the structures can be strengthened and have greater life expectancy.